Der Gott der Waren: Die ökonomische Theorie und ihr Geld - Stützle, Ingo (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2015)
Capitalism is essentially a money economy: money makes the world go round. But there’s a big ambiguity in which sense money is relevant. The confusion about money based on the comprehension of what capitalism is – irrespective of if the position is critical or a&rmative. The article provide a survey of the main theories, the paradigms of political economy and their conceptualization of money: Classic/Neoclassic, Keynesian and Marxian Theory. It also discusses three relevant problem areas in money theory: inflation and the distinction of money and credit, which is important to understand the modern banking system with central bank and corporate bank.